Uji Kriteria Manajemen dalam Pengelolaan Air Limbah Domestik Terpusat - Siswati, Muji; Syafrudin, Syafrudin; Sriyana, Sriyana (MEDIA KOMUNIKASI TEKNIK SIPIL, 2017)
Sanitation infrastructure is one of the basic needs of society and has a strategic role in improving the health and welfare of the community. The Indonesian government has built centralized domestic waste water infrastructure in 13 cities until 2014. According to USAID (2006) and AusAID (2013), idle capacity and cost recovery in the centralized domestic waste water system is still a major problem. Therefore, it needs to be done assessment management criteria of centralized domestic waste water management. This research is done by three-stage, that is construction models of a relationship of interdependence between management criteria; assessment of model suitability that has been constructed using SEM method; and calculate the weight of each management criteria using ANP method. The management criteria used on this study consist of: performance management, technical, institutional, regulatory, financing, and public participation. The weight of each criteria using models that have been assessment for their suitability, are: performance management (75.37%), financing (8.83%), public participation (8.39%), technical (3.56%), regulatory (2.36%) and institutional (1:49%). The global weight of sub criteria with most critical weight and should be a priority concern are sustainability (48.20%), public acceptance (14.90% 0, reliability (9.30%), willingness to pay (5.20%), and cost recovery (4.62%).